La producción y la cadena de valor de las artesanías en el Mercado “El Pasaje” de Baños de Agua Santa, provincia de Tungurahua. - Palacios Perlaza, David Israel (2026)
Handicraft production, based on the transformation of natural raw materials through traditional techniques, not only reflects the region's cultural identity but also serves as a key driver of the community's socioeconomic development. However, this sector faces challenges in terms of competitiveness, market access, innovation, and sustainability. The main objective is to propose a value chain business model to help artisans at El Pasaje Market gain a greater competitive advantage. This approach enables the identification of improvement opportunities across key processes, including raw material acquisition, artisanal transformation, and the commercialization of finished products. In El Pasaje Market, located in Baños de Agua Santa, there are 57 registered workspaces for artisans dedicated to the daily production and sale of handicrafts, products made from various materials are sold here, attracting tourists and merchants from different provinces across the country. The main issue for producers is the lack of a business model that would give artisans a competitive edge against their rivals.